MANAJEMEN PENGEMBANGAN KOMPETENSI PROFESIONALISME GURU DI MTs SHIROTOL ILMIYAH KEDUNGDUNG - Badrut tamam; Nurul Huda (AL -ALLAM, 2026)
Education is a crucial element for every individual, as it fosters the development of high-quality human resources. Through schooling, individuals acquire proper knowledge and learn valuable skills, attitudes, and proficiencies from their teachers. Education is a process aimed at developing an individual's abilities and potential across various dimensions—knowledge, skills, and attitudes alike. This study aims to address three primary questions: first, how is the professional competence development for teachers planned at MTs Shirotol Ilmiyah Kedungdung? Second, how is this professional competence development implemented? And third, how is the professional competence development evaluated at the school? This research employs a qualitative, descriptive approach. Data collection techniques included observation, interviews, and document analysis. Informants included the principal, the vice-principal (specifically the curriculum coordinator), teachers, and students. Data validity was verified through source and technique triangulation, as well as in-depth observation. The research findings indicate that, first, the planning of professional competence development at MTs Shirotol Ilmiyah Kedungdung is conducted in a structured manner, involving the identification of teacher needs, the formulation of annual work programs, goal setting, budget allocation, and activity scheduling—all aligned with the school's vision, mission, and objectives. This planning process is participatory, involving the principal, vice-principal, and teachers to ensure the designed programs meet the actual needs for enhancing teacher competence. Second, the implementation of professional competence development at MTs Shirotol Ilmiyah Kedungdung involves various activities such as training sessions, seminars, workshops, and Subject Teacher Forums (MGMP). The principal plays multiple roles—leader, motivator, facilitator, supervisor, and evaluator—in supporting the enhancement of teacher competence. Although challenges such as limited budgets, time constraints, and a lack of supporting facilities persist, the school strives to overcome them through collaboration with various parties, the optimization of existing resources, and by motivating teachers to remain actively engaged in professional development activities. Third, the evaluation of professional competence development for teachers at MTs Shirotol Ilmiyah Kedungdung is conducted periodically through classroom supervision, monitoring of instructional implementation, teacher performance assessment, evaluation meetings, and reflection on the outcomes of the programs that have been implemented. Keywords: development, competence, teacher professionalism, MTs Shirotol Ilmiyah